Processing of zero-derived words in English: An fMRI investigation - Pliatsikas, C; Wheeldon, L; Lahiri, A; Hansen, P (Elsevier, 2014)
Derivational morphological processes allow us to create new words (e.g. punish (V) to noun (N) punishment) from base forms. The number of steps from the basic units to derived words often varies (e.g., nationality < national < nation : two-steps) and there is evidence that complex derivations cause more brain activity than simple ones ( Meinzer, Lahiri, Flaisch, Hannemann, & Eulitz, 2009). However, all studies to date have investigated derivational processes in which morphological complexity is related to a change in surface form. It is therefore unclear whether the effects reported are attributable to underlying morphological complexity or to the processing of multiple surface morphemes. Here we report the first study to investigate morphological processing where derivational steps are not overtly marked (e.g., bridge-N>bridge-V) i.e., zero-derivation ( Aronoff, 1980). We compared the processing of one-step (soaking < soak-V) and two-step ( bridging < bridge -V< bridge -N) derivations together with monomorphemic control words (grumble) in an fMRI experiment. Participants were presented with derived forms of words (soaking, bridging) in a lexical decision task. Although the surface derived -ing forms can be contextually participles, gerunds, or even nouns, they are all derived from verbs since the suffix -ing can only be attached to verb roots. Crucially, the verb root is the basic form for the one-step words, whereas for the two-step words the verb root is zero derived from a basic noun. Significantly increased brain activity was observed for complex (one-step and two-step) versus simple (zero-step) forms in regions involved in morphological processing, such as the left inferior frontal gyrus (LIFG). Critically, activation was also more pronounced for two-step compared to one-step forms. Since both types of derived words have the same surface structure, our findings suggest that morphological processing is based on underlying morphological complexity, independent of overt affixation. This study is the first to provide evidence for the processing of zero derivation, and demonstrates that morphological processing cannot be reduced to surface form-based segmentation.